2019
DOI: 10.1186/s12985-019-1266-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effects of patchouli alcohol against influenza a virus through targeting cellular PI3K/Akt and ERK/MAPK signaling pathways

Abstract: BackgroundPatchouli alcohol (PA) is a tricyclic sesquiterpene extracted from Pogostemonis Herba, which is a traditional Chinese medicine used for therapy of inflammatory diseases. Recent studies have shown that PA has various pharmacological activities, including anti-bacterial and anti-viral effects.MethodsIn this study, the anti-influenza virus (IAV) activities and mechanisms were investigated both in vitro and in vivo. The inhibitory effects of PA against IAV in vitro were evaluated by plaque assay and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…As revealed from the KEGG pathway enrichment analysis, SHL oral liquid might produce therapeutic effects primarily by regulating PI3K-Akt signaling pathway, thyroid hormone signaling pathway, human cytomegalovirus infection, and human papillomavirus infection. PI3K/ Akt signaling pathway is known to associate with viral replication and inflammatory response [65,66]. Cellular PI3K/Akt signaling pathway may inhibit the lytic infections of both RNA and DNA viruses, thus some inhibitors of PI3K or its downstream signal Akt could significantly block virus entry and replication [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As revealed from the KEGG pathway enrichment analysis, SHL oral liquid might produce therapeutic effects primarily by regulating PI3K-Akt signaling pathway, thyroid hormone signaling pathway, human cytomegalovirus infection, and human papillomavirus infection. PI3K/ Akt signaling pathway is known to associate with viral replication and inflammatory response [65,66]. Cellular PI3K/Akt signaling pathway may inhibit the lytic infections of both RNA and DNA viruses, thus some inhibitors of PI3K or its downstream signal Akt could significantly block virus entry and replication [66].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/ Akt signaling pathway is known to associate with viral replication and inflammatory response [65,66]. Cellular PI3K/Akt signaling pathway may inhibit the lytic infections of both RNA and DNA viruses, thus some inhibitors of PI3K or its downstream signal Akt could significantly block virus entry and replication [66]. The activation of the PI3K/AKT pathway was responsible for the increased levels of adenosine diphosphate and promoted platelet activation, leading to anabatic vascular permeability and pulmonary inflammatory responses [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…PA has been found to have anti-influenza A (IAV) effect in vitro, while H1N1 virus is the most sensitive to PA [135]. In addition, Yunjia Yu et al found that intracellular PI3K/Akt and ERK/MAPK signaling pathways may be involved in the anti-IAV effect of PA and PA significantly inhibits the in vitro proliferation of different IAV, suggesting that PA may block IAV infection by directly killing viral particles and interfering with some early stages after viral adsorption [136]. Another study showed that PA also has an effect against influenza virus (IFV) in vivo and enhances protection against IFV infection in mice by enhancing host immune responses and attenuating systemic and pulmonary inflammatory responses [137].…”
Section: Patchouli Alcoholmentioning
confidence: 99%
“…Three distinct MAPKs have been identified on the basis of the respective terminal MAPK components, namely, extracellular signal-regulated kinases (ERK), MAPK p38, and c-Jun N-terminal kinases (JNK) [27][28][29]. The MAPK pathways play vital role in viral infection including foot-and-mouth disease and influenza [30,31]. Severe acute respiratory syndrome coronavirus(SARS-CoV) 3b protein induces activator protein-1 (AP-1) transcriptional activity through activation of JNK and ERK pathways, and SARS-CoV 3b protein has an important role in the stimulation of AP-1-dependent genes, especially proinflammatory cytokines causing the cytokine storm during SARS virus infection [32].…”
Section: Introductionmentioning
confidence: 99%